Cerebral Infarction in Young Marijuana Smokers - Case Reports - Šimůnek, Libor; Krajina, Antonín; Herzig, Roman; Vališ, Martin (Acta Medica, 2018)
INTRODUCTION: Causality of marijuana abuse with development of ischemic stroke has been indicated by numerous case reports and epidemiological studies. As a possible pathophysiological mechanism, the most common consideration is cardiac embolization during paroxysmal atrial fibrillation, systemic hypotension or multifocal intracerebral vasoconstriction. CASE REPORTS: We present three case reports of marijuana consumers who were admitted to our comprehensive stroke center due to ischemic stroke within 18-month period of our investigation. In one case, the cause of stroke was not related to the use of marijuana, it was a manifestation of antiphospholipid syndrome. In two cases the association with the abuse of this drug is probable but not certain. In both these cases, an isolated occlusion in vertebrobasilar arterial system was detected, without finding of a cerebral vessels stenosis. Although we did not register the atrial fibrillation, we consider cardiac embolization as probable etiological mechanism of stroke in both cases. In one case, paradoxical embolization due to the persistent foramen ovale represents another potential etiological mechanism. CONCLUSIONS: Cannabinoid use may cause ischemic stroke, especially in the younger age category. Therefore, in these patients we recommend focusing on the history of cannabinoid abuse and carry out toxicological urine tests.
Keywords: abúzus marihuany; dospělí; Cerebral Infarction; mladý dospělý; Marijuana Smoking; kouření marihuany; Angiography, Digital Subtraction; lidé; cerebrální infarkt; Female; digitální subtrakční angiografie; mužské pohlaví; Young Adult; Male; Marijuana Abuse; Adult; ženské pohlaví; Humans